How To Build Continuance Intention On Jenius App Users - Tri Wahyu Oktavendi; Ike Arisanti (TIJAB (The International Journal of Applied Business), 2021)
The availability of various kinds of transaction services via smartphones will certainly affect its users. The theme of Financial Technology (Fintech) is also developing which includes transactions through smartphone applications. The big question arises, namely what are the factors that influence Jenius-App users to be intense in using the application? Its Benefit? Or its Risk?. This study tries to examine the factors that affect Continuance Intention on Jenius App users. Smart PLS 15 is used in this study by using Outer Model and Inner Model. The Results show that it is only three hypotheses are accepted. First, Perceived Usefulness Affect Continuance Intention. Second, Perceived Ease of Use Affect Perceived Usefulness. Third, Perceived Risk Affect Perceived Ease of Use.